Fabricated Wire Acrylic Occlusal Splint for the Management of Mandibular and Maxillary Fractures - Kiran M Patel (Indian Journal of Plastic Surgery)
Fractures of the mandible and maxilla are usually treated by reduction and immobilization by interdental wiring and intermaxillary fixation. Inability to open the mouth for a period of 5-6 weeks is a disadvantage of this method. Recent techniques like rigid plate fixation help to reduce this period of immobilization of the jaws but it required the necessary equipment and may prove to be expensive in a public hospital system. We have fabricated wire acrylic occlusal splint which has been used in 18 patients for the management of mandibular or maxillary fractures over a period of one year. The mouth remains open during the course of treatment and it greatly helps in oral hygiene. Patient is permitted to take liquids and swallow semi-solid diets by mouth. The splint is removed after bony union is confirmed. We have used this technique in 5 children and 13 adults and has been used both for mandibular and maxillary fractures. There has only been one complication of an occlusal disturbance which was corrected later by dental treatment.